Release Film
A 4-methyl-1-pentene-based release film with specific polymer compositions addresses adherence and visibility issues, enabling residue-free microfabrication and excellent heat resistance for fiber-reinforced resins.
Patent Information
- Application Number
- JP2021048869
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-23
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-03-23
AI Technical Summary
Conventional 4-methyl-1-pentene resin compositions used as release films do not adequately adhere to molded objects during microfabrication, leaving residues and failing to provide good visibility, especially when used with fiber-reinforced resins.
A release film composed of 60 to 95% by mass of 4-methyl-1-pentene (co)polymer (A) and 5 to 40% by mass of 4-methyl-1-pentene copolymer (B), with specific structural units, intrinsic viscosity, melting points, and linear expansion coefficients, ensuring excellent heat resistance, mold releasability, and visibility.
The film allows for microfabrication of molded objects without residue, maintains good visibility, and adheres well to irregular surfaces, providing equivalent heat resistance and mold release properties to conventional films.
Smart Images

Figure 0007599360000001 
Figure 0007599360000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a single-layer or multi-layer release film having a layer containing a 4-methyl-1-pentene polymer. [Background technology]
[0002] 4-Methyl-1-pentene-α-olefin copolymers, which have 4-methyl-1-pentene as the main constituent monomer, are widely used in various applications due to their excellent heat resistance, releasability, and chemical resistance. For example, films containing the copolymers are used in various release films, such as release films for fiber-reinforced resin molding, release films for printed wiring board manufacturing, release films for composite material molding, and release paper for synthetic leather manufacturing, taking advantage of their excellent releasability and other characteristics (see Patent Document 1).
[0003] For example, when manufacturing a flexible printed circuit board, a process is usually carried out in which a coverlay film is laminated on a substrate on which a circuit pattern is formed, and a heat press molding process is carried out in which the obtained laminate is sandwiched between heat press plates and heated and pressed.
[0004] During the heat press molding process, in order to prevent the coverlay film and the heat press plate from adhering to each other, a fluorine-based film made of polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, polyvinyl fluoride, or the like, or a release film made of polymethylpentene film, polybutylene terephthalate, syndiotactic polystyrene, or the like is used between them (see Patent Document 2).
[0005] As the release film, it has been proposed to use a film made of poly-4-methyl-1-pentene resin, because it has excellent heat resistance, releasability after heating and pressing, and excellent conformability to the circuit board. Poly-4-methyl-1-pentene has a high melting point of 235°C, so it has excellent heat resistance and releasability even in the molding of copper-clad laminates, which is carried out at a temperature of about 180°C (see Patent Document 3).
[0006] Patent Document 4 discloses a release film having excellent heat resistance and stain resistance. On the other hand, a protective film made of a 4-methyl-1-pentene polymer and an olefin elastomer (Patent Document 5), a film formed from a composition of a 4-methylpentene polymer and an olefin elastomer (Patent Document 6), and release paper for producing synthetic leather (Patent Document 7) are also known. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2010-027745 A [Patent Document 2] JP 2005-350601 A [Patent Document 3] JP 2014-098138 A [Patent Document 4] JP 2016-098257 A [Patent Document 5] International Publication No. 2015 / 012274 [Patent Document 6] International Publication No. 2013 / 099876 [Patent Document 7] JP 2017-074775 A Summary of the Invention [Problem to be solved by the invention]
[0008] On the other hand, fiber-reinforced resin molding is usually performed by sandwiching a release film between a mold and a fiber-reinforced resin, heating and pressurizing the molded body, and then releasing the molded body from the mold. In this case, the release film is required to have no film residue on the molded body when peeled off, and to have good visibility when the release film adheres to the molded body, but conventional release films could not fully meet these requirements. In addition, conventional 4-methyl-1-pentene resin compositions do not conform well to molded bodies, and when used as a release film during fine processing of molded bodies, it is difficult to process them into the desired molded body because they cannot follow unevenness.
[0009] The present invention has been made in consideration of the above circumstances, and aims to provide a release film that has heat resistance and releasability equivalent to conventional release films, allows for fine processing of molded bodies, leaves no film residue on the molded body when peeled off, and has good visibility when attached to a molded body. [Means for solving the problem]
[0010] An example of a specific means for solving the above problem is as follows. [1] 60 to 95 mass% of a 4-methyl-1-pentene (co)polymer (A) satisfying the following requirements (Aa) to (Ac); 5 to 40% by mass of a 4-methyl-1-pentene copolymer (B) satisfying the following requirements (Ba) to (Bc) (the total amount of the (co)polymer (A) and the copolymer (B) is taken as 100% by mass), A layer made of a composition (X) containing A single-layer or multi-layer release film with a total light transmittance of less than 80%, measured using a 30μm thick film in accordance with JIS K7136. (Aa) The content of structural units (P) derived from 4-methyl-1-pentene is 90 to 100 mol %, and the content of structural units (AQ) derived from ethylene and an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is 0 to 10 mol % (the total content of structural units (P) and structural units (AQ) is 100 mol %). (Ab) The intrinsic viscosity [η] measured in decalin at 135°C is 0.5 to 5.0 dl / g. (Ac) The melting point (Tm) measured by DSC is in the range of 200 to 250°C. (Ba) The content of structural units (P) derived from 4-methyl-1-pentene is 65 to 97 mol %, and the content of structural units (BQ) derived from at least one selected from ethylene and an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is 3 to 35 mol % (the total content of structural units (P) and structural units (BQ) is 100 mol %). (Bb) The intrinsic viscosity [η] measured in decalin at 135°C is 0.5 to 5.0 dl / g. (Bc) The melting point (Tm) measured by DSC is not confirmed or is in the range of 100 to 199°C. [2] The linear expansion coefficient from 23°C to 180°C is 1.0 to 1.7×10 in the MD direction. -4 / °C, and a ratio of the linear expansion coefficient in the MD direction to the linear expansion coefficient in the TD direction (MD / TD) is 1.0 to 2.5. [3] The release film according to [1] or [2], wherein the structural unit (BQ) is a structural unit derived from at least one selected from ethylene and an α-olefin having 3 to 4 carbon atoms. [4] The release film according to any one of [1] to [3], further comprising a coloring component (C). [5] The release film according to any one of [1] to [4], which is for use in fiber-reinforced resin molding. Effect of the Invention
[0011] The release film of the present invention has the same heat resistance and releasability as conventional release films, allows for fine processing of molded bodies, leaves no film residue on the molded body when peeled off, and has good visibility when attached to the molded body. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] <Release film> The release film according to the present invention has a layer made of a composition (X) containing a 4-methyl-1-pentene (co)polymer (A) (hereinafter also simply referred to as "polymer (A)") and a 4-methyl-1-pentene copolymer (B) (hereinafter also simply referred to as "copolymer (B)") described below. In the present invention, the term "(co)polymer" includes the concepts of both a homopolymer and a copolymer.
[0013] [Composition (X)] The composition (X) is a composition containing a polymer (A) and a copolymer (B). The polymer (A) and the copolymer (B) will be described below.
[0014] <Polymer (A)> The polymer (A) satisfies the following requirements (Aa) to (Ac): The polymer (A) contained in the composition (X) may be one type, or two or more types.
[0015] Requirement (Aa): The content of the structural unit (P) derived from 4-methyl-1-pentene is 90 to 100 mol %, and the content of the structural unit (AQ) derived from ethylene and an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is 0 to 10 mol % (the total content of the structural unit (P) and the structural unit (AQ) is 100 mol %).
[0016] The content of the structural unit (P) in the polymer (A) is 90 to 100 mol %, and preferably 90 to 96 mol %, and the content of the structural unit (AQ) (when there are two or more types of structural units (AQ), the total content of said two or more types) is 0 to 10 mol %, and preferably 4 to 10 mol % (with the total content of the structural unit (P) and the structural unit (AQ) being 100 mol %).
[0017] When the content of the structural unit (P) in the polymer (A) is 90 mol % or more, there is an advantage in that a release film having excellent heat resistance and an elastic modulus suitable for handling can be obtained. Examples of the α-olefin having 3 to 20 carbon atoms other than 4-methyl-1-pentene that forms the structural unit (AQ) include propylene, 1-butene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene, and 1-eicosene. The ethylene and the α-olefin may be one type or two or more types.
[0018] As the ethylene and α-olefin forming the structural unit (AQ), from the viewpoint of imparting appropriate elastic modulus, softness and flexibility to the layer of the composition (X), olefins having 8 to 18 carbon atoms, for example, 1-octene, 1-decene, 1-tetradecene, 1-hexadecene, 1-heptadecene and 1-octadecene are preferred.
[0019] The polymer (A) may contain other structural units besides the structural unit (P) and the structural unit (AQ) as long as the effects of the present invention are not impaired. The content of the other structural units is, for example, 0 to 10 mol % (wherein the total content of the structural unit (P) and the structural unit (AQ) is 100 mol %).
[0020] Specific examples of the monomers that form the other structural units are the same as the specific examples of the monomers that form the other structural units that can be contained in the copolymer (B) described below. The content (mol%) of each structural unit in the polymer (A) is, like that of the copolymer (B) described later, 13 This value was measured using a C-NMR measurement method.
[0021] Requirement (Ab): The intrinsic viscosity [η] measured in decalin at 135°C is 0.5 to 5.0 dl / g. The intrinsic viscosity [η] of the polymer (A) measured in decalin solvent at 135° C. is 0.5 to 5.0 dl / g, preferably 1.0 to 4.0 dl / g, more preferably 1.0 to 3.5 dl / g, and even more preferably 1.0 to 3.0 dl / g. When the intrinsic viscosity [η] of the polymer (A) is within the above range, the amount of low molecular weight components is small, so that the layer made of the composition (X) becomes less sticky, and a laminate can be formed by extrusion lamination.
[0022] The intrinsic viscosity [η] of the polymer (A) is a value measured by the following method using an Ubbelohde viscometer. 20 mg of polymer (A) is dissolved in 25 ml of decalin to obtain a decalin solution, and then the specific viscosity ηsp is measured using an Ubbelohde viscometer in an oil bath at 135°C. This decalin solution is diluted by adding 5 ml of decalin, and the specific viscosity ηsp is measured in the same manner as above. This dilution procedure is repeated two more times, and the value of ηsp / C when the concentration (C) is extrapolated to 0 is taken as the limiting viscosity [η] (unit: dl / g) (see the formula below). [η]=lim(ηsp / C) (C→0)
[0023] Requirement (Ac): The melting point (Tm) measured by DSC is in the range of 200 to 250°C. The melting point (Tm) of the polymer (A) is in the range of 200 to 250° C., preferably 200 to 245° C., and more preferably 200 to 240° C. By using the polymer (A) having a Tm in the above range, it is possible to obtain a release film that has a suitable elastic modulus compared to a polymer having a Tm higher than the above range, and has better heat resistance compared to a polymer having a Tm lower than the above range.
[0024] The Tm of the polymer (A) is a value measured by the following method in accordance with JIS K7121 using a differential scanning calorimetry (DSC). Approximately 5 mg of polymer (A) is sealed at room temperature in an aluminum pan for measurement of a differential scanning calorimeter (DSC220C type) manufactured by Seiko Instruments Inc., and heated from room temperature to 280°C at a rate of 10°C / min. In order to completely melt the polymer (A), it is held at 280°C for 5 minutes, and then cooled to -50°C at a rate of 10°C / min. After holding at -50°C for 5 minutes, it is heated a second time to 280°C at a rate of 10°C / min, and the temperature at which a peak is observed during this second heating is taken as the melting point (Tm) of the polymer. When multiple peaks are detected, the peak detected on the highest temperature side is used. In addition to the above requirements (Aa) to (Ac), the polymer (A) preferably satisfies any one of the following requirements.
[0025] Requirement (Ad): The density of the polymer (A) measured in accordance with JIS K7112 (density gradient tube method) is preferably 820 to 850 kg / m 3 , more preferably 825 to 840 kg / m 3 , particularly preferably 830 to 835 kg / m 3 When the density is within the above range, the mechanical strength of the layer made of composition (X) tends to be higher than when the density is lower than the above range, and the impact strength of the layer made of composition (X) tends to be higher than when the density is higher than the above range.
[0026] Requirement (Ae): The melt flow rate (MFR) of the polymer (A), measured in accordance with ASTM D1238 at 260°C under a load of 5.0 kg, is preferably in a range in which the polymer (A) can be easily mixed with the copolymer (B) described below in an extruder or the like and can be co-extruded, and is preferably 0.5 to 200 g / 10 min, more preferably 1 to 150 g / 10 min, and particularly preferably 1 to 100 g / 10 min. When the MFR is in the above range, the composition (X) can be easily extruded to a relatively uniform film thickness.
[0027] Requirement (Af): The molecular weight distribution (Mw / Mn) of the polymer (A) is preferably 1.0 to 7.0, and more preferably 2.0 to 6.0. The molecular weight distribution (Mw / Mn) of the polymer (A) is a value calculated by the method described in the Examples.
[0028] Requirement (Ag): From the viewpoint of obtaining a layer made of the composition (X) that is difficult to break, the polymer (A) is preferably a polymer with high crystallinity. The highly crystalline polymer may be either a polymer having an isotactic structure or a polymer having a syndiotactic structure, but a polymer having an isotactic structure is particularly preferable and is also easily available. Furthermore, the stereoregularity of the polymer (A) is not particularly limited, but it is preferable that the polymer (A) has a stereoregularity that allows the composition (X) to be molded into a film and a film having a strength sufficient to withstand the intended use can be obtained.
[0029] (Method for producing polymer (A)) The polymer (A) may be produced by polymerizing olefins, or by pyrolysis of a high molecular weight 4-methyl-1-pentene polymer. The polymer (A) may be purified by solvent fractionation, which separates the polymers based on the difference in solubility in a solvent, or molecular distillation, which separates the polymers based on the difference in boiling point.
[0030] When the polymer (A) is produced by a polymerization reaction, the melting point, stereoregularity, molecular weight, etc. can be controlled by adjusting, for example, the amount of 4-methyl-1-pentene and the α-olefin to be copolymerized as necessary, the type of polymerization catalyst, the polymerization temperature, the amount of hydrogen added during polymerization, etc. The method for producing the polymer (A) by a polymerization reaction may be a known method. The polymer (A) can be produced by a method using a known catalyst such as a Ziegler-Natta catalyst or a metallocene catalyst, and preferably by using a metallocene catalyst. On the other hand, when the polymer (A) is produced by pyrolysis of a 4-methyl-1-pentene polymer having a higher molecular weight, the molecular weight can be controlled to a desired value by controlling the temperature and time of pyrolysis.
[0031] The polymer (A) may be a commercially available polymer such as TPX manufactured by Mitsui Chemicals Inc. in addition to those produced as described above.
[0032] <Copolymer (B)> The copolymer (B) satisfies the following requirements (Ba) to (Bc): The copolymer (B) contained in the composition (X) may be one type or two or more types.
[0033] Requirement (Ba): The content of the structural unit (P) derived from 4-methyl-1-pentene is 65 to 97 mol %, and the content of the structural unit (BQ) derived from at least one selected from ethylene and an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is 3 to 35 mol % (the total content of the structural unit (P) and the structural unit (BQ) is 100 mol %).
[0034] The content of the structural unit (P) is preferably from 65 to 95 mol %, and more preferably from 65 to 90 mol %. When the content of the structural unit (P) is within the above range, the film has excellent releasability and heat resistance.
[0035] The content of the structural unit (BQ) (when there are two or more types of structural unit (BQ), the total content of said two or more types) is preferably 5 to 35 mol %, and more preferably 10 to 35 mol %. When the content of the structural unit (BQ) in the copolymer (B) is within the above range, the unevenness-following ability of the resulting film is improved.
[0036] As the α-olefin having 3 to 20 carbon atoms other than ethylene and 4-methyl-1-pentene, which forms the structural unit (BQ), from the viewpoint of further reducing the anisotropy of the tensile elongation at break and the anisotropy of the tear strength of the obtained film and also improving the impact resistance, preferred are ethylene, propylene, 1-butene, 1-hexene, 1-octene, 1-decene, 1-hexadecene, and 1-octadecene, more preferred are ethylene and α-olefins having 3 to 4 carbon atoms, i.e., propylene and 1-butene, and particularly preferred is propylene.
[0037] As the ethylene and α-olefin that form the structural unit (BQ), one type may be used alone, or two or more types may be used together. When the polymer (A) contains a structural unit (AQ), the structural unit (BQ) may be the same as or different from the structural unit (AQ).
[0038] Copolymer (B) may contain other structural units besides the structural unit (P) and the structural unit (BQ) as long as the effects of the present invention are not impaired. The content of the other structural units is, for example, 0 to 10 mol % (wherein the total content of the structural unit (P) and the structural unit (BQ) is 100 mol %).
[0039] Examples of the monomer that forms the other structural units include cyclic olefins, aromatic vinyl compounds, conjugated dienes, non-conjugated polyenes, functional vinyl compounds, hydroxyl group-containing olefins, and halogenated olefins.
[0040] As the cyclic olefin, aromatic vinyl compound, conjugated diene, non-conjugated polyene, functional vinyl compound, hydroxyl group-containing olefin and halogenated olefin, for example, the compounds described in paragraphs 0035 to 0041 of JP-A No. 2013-169685 can be used. As the monomer forming the other structural units, vinylcyclohexane and styrene are particularly preferred.
[0041] When the copolymer (B) contains the other structural units, the other structural units may be contained in one type only, or in two or more types. The content (mol%) of each structural unit in copolymer (B) is as follows: 13 This was measured using a C-NMR measurement method.
[0042] ~Conditions~ Measurement equipment: Nuclear magnetic resonance equipment (ECP500 type, manufactured by JEOL Ltd.) Observed nucleus: 13C (125MHz) Sequence: Single pulse proton decoupling Pulse width: 4.7μsec (45° pulse) Repeat time: 5.5 seconds Number of times: 10,000 or more Solvent: orthodichlorobenzene / deuterated benzene (volume ratio: 80 / 20) mixed solvent Sample concentration: 55mg / 0.6mL Measurement temperature: 120℃ Chemical shift reference value: 27.50 ppm
[0043] Requirement (Bb): The intrinsic viscosity [η] measured in decalin at 135°C is 0.5 to 5.0 dl / g.
[0044] The copolymer (B) has an intrinsic viscosity [η] measured in decalin solvent at 135° C. of 0.5 to 5.0 dl / g, preferably 0.5 to 4.0 dl / g, more preferably 0.5 to 3.5 dl / g, and particularly preferably 1.0 to 3.5 dl / g. The intrinsic viscosity [η] of the copolymer (B) is a value measured in the same manner as the intrinsic viscosity [η] of the polymer (A).
[0045] Requirement (Bc): The melting point (Tm) measured by DSC is not confirmed or is in the range of 100 to 199°C.
[0046] The melting point (Tm) of the copolymer (B) is either not confirmed as a melting point (Tm) measured by DSC or is in the range of 100 to 199°C, preferably not confirmed as a melting point (Tm) measured by DSC or is in the range of 110 to 180°C, more preferably not confirmed as a melting point (Tm) measured by DSC or is in the range of 110 to 160°C, particularly preferably not confirmed as a melting point (Tm) measured by DSC or is in the range of 125 to 150°C.
[0047] The Tm of the copolymer (B) is a value measured by the same method as for the Tm of the polymer (A). In addition to the above requirements (Ba) to (Bc), the copolymer (B) preferably satisfies any one of the following requirements.
[0048] Requirement (Bd): The molecular weight distribution (Mw / Mn) of the copolymer (B) is preferably 1.0 to 3.5, more preferably 1.1 to 3.0, from the viewpoints of stickiness and appearance of the layer made of the composition (X). The Mw / Mn of the copolymer (B) is a value calculated by the method described in the Examples.
[0049] Requirement (Be): The density of the copolymer (B) measured in accordance with JIS K7112 (density gradient tube method) is preferably 825 to 860 kg / m from the viewpoint of handleability. 3 , more preferably 830 to 860 kg / m 3 , particularly preferably 830 to 850 kg / m 3 It is.
[0050] Requirement (Bf): The melt flow rate (MFR) of the copolymer (B), measured in accordance with ASTM D1238 at 230°C under a load of 2.16 kg, is preferably 0.1 to 100 g / 10 min, more preferably 0.5 to 50 g / 10 min, and particularly preferably 0.5 to 30 g / 10 min, from the viewpoint of fluidity during molding of the composition (X).
[0051] (Method for producing copolymer (B)) The copolymer (B) can be synthesized using a conventionally known metallocene catalyst system, for example, by the methods described in WO 2005 / 121192, WO 2011 / 055803, WO 2014 / 050817, and the like.
[0052] <Composition (X)> In the composition (X), the content of the polymer (A) relative to the total of the polymer (A) and the copolymer (B) (100% by mass) is 60 to 95% by mass, preferably 70 to 90% by mass, and more preferably 75 to 90% by mass. The content of the copolymer (B) is 5 to 40% by mass, preferably 10 to 30% by mass, and more preferably 10 to 25% by mass.
[0053] When the content of the polymer (A) is within the above range, a film having superior releasability and heat resistance compared to a content less than the above range can be obtained, and a film having superior conformability to irregularities compared to a content greater than the above range can be obtained.
[0054] By blending the copolymer (B) with the polymer (A), flexibility can be imparted to the release film, and the balance of the linear expansion coefficient ratio (MD / TD) described later can be improved.
[0055] If the content of copolymer (B) relative to polymer (A) is too high, the balance of the ratio of linear expansion coefficients (MD / TD) will be good. However, when the release film is used to mold, for example, a carbon fiber composite material (CFRP), the release film will penetrate into the carbon fibers, causing a problem that the film will tear when peeled off.
[0056] From the viewpoint of heat resistance, the composition (X) preferably has a TMA softening temperature of 200° C. or higher (e.g., 200 to 240° C.) measured in accordance with JIS K7196. The TMA softening temperature can be increased, for example, by reducing the content of the copolymer (B) or by reducing the content of the structural unit (AQ) in the polymer (A).
[0057] The composition (X) can be obtained by mixing the polymer (A) and the copolymer (B) in the above-mentioned ratio, but the composition (X) may also be obtained, for example, by a polymerization reaction of olefins. When the composition (X) is obtained by mixing the polymer (A) and the copolymer (B), the mixing method is not particularly limited, but examples thereof include a method in which the compounds are mixed in a twin-screw extruder, or pellets are dry-blended, etc.
[0058] Composition (X) may further contain various additives such as weathering stabilizers, heat stabilizers, antioxidants, UV absorbers, antistatic agents, slip prevention agents, antiblocking agents, antifogging agents, nucleating agents, lubricants, pigments, dyes, antioxidants, hydrochloric acid absorbers, inorganic or organic fillers, organic or inorganic foaming agents, crosslinking agents, crosslinking assistants, adhesives, softeners, and flame retardants, and resins other than polymer (A) and copolymer (B) within the scope of the present invention. The content of components other than polymer (A) and copolymer (B) in composition (X) is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, based on 100 parts by mass of the total of polymer (A) and copolymer (B).
[0059] [Release film] In the present invention, the term "film" is used for convenience, and is a general term for planar molded products, and this concept includes sheets, membranes, tapes, and the like.
[0060] The composition (X) can be processed into a desired molded article, for example, a film, a sheet, etc., by various molding methods such as extrusion cast molding, extrusion lamination molding, calendar molding, inflation molding, roll molding, etc. It is also preferable that the molded article obtained by the above-mentioned molding method is further uniaxially or biaxially stretched.
[0061] The release film of the present invention has a total light transmittance of less than 80%, preferably 79% or less, more preferably 78% or less, measured using a film having a thickness of 30 μm according to JIS K7136. When the total light transmittance is within the above range, the release film of the present invention has good visibility, and when the release film of the present invention is attached to a molded body, the attached release film can be easily recognized visually. When the release film has high transmittance and low visibility, it becomes difficult to recognize the attached release film, and there is a risk that the film will remain after peeling.
[0062] The release film of the present invention may contain a coloring component (C) such as a colorant in order to obtain the above-mentioned visibility. The coloring component (C) may be contained in the composition (X). The content of the coloring component (C) in the release film of the present invention is preferably 4 parts by mass or more, more preferably 5 parts by mass or more, and even more preferably 6 parts by mass or more, when the total of the polymer (A) and the copolymer (B) is 100 parts by mass.
[0063] As the coloring component (C), for example, organic or inorganic pigments can be used alone or in combination of two or more kinds. Among the pigments, pigments with high color development and high heat resistance are preferred, and organic pigments are usually used. Specific examples of organic pigments are shown below by color index numbers. In addition, dyes can be contained as colorants within the range that does not impair the effects of the present invention.
[0064] Examples of blue pigments include CI Pigment Blue 1, 1:2, 9, 14, 15, 15:1, 15:2, 15:3, 15:4, 15:6, 16, 17, 19, 25, 27, 28, 29, 33, 35, 36, 56, 56:1, 60, 61, 61:1, 62, 63, 66, 67, 68, 71, 72, 73, 74, 75, 76, 78, and 79. Examples of white pigments include CI Pigment White 6, 18, and 21. Examples of green pigments include CI Pigment Green 1, 2, 4, 7, 8, 10, 13, 14, 15, 17, 18, 19, 26, 36, 45, 48, 50, 51, 54, 55, 58, 59, 62, and 63. Examples of inorganic pigments include metal oxide powders such as barium sulfate, zinc oxide, lead sulfate, yellow lead, zinc yellow, red iron oxide (red iron (III) oxide), cadmium red, ultramarine, Prussian blue, chromium oxide green, cobalt green, amber, titanium black, synthetic iron black, titanium oxide, and iron tetroxide, metal sulfide powders, and metal powders.
[0065] As a method for imparting visibility to the release film of the present invention, in addition to the method of incorporating a coloring component (C), for example, a method of embossing the film can be mentioned.
[0066] The release film of the present invention has a linear expansion coefficient of 1.0 to 1.7 × 10 in the MD direction from 23 ° C. to 180 ° C. -4 / °C, and is preferably 1.04 to 1.6 × 10 -4 / °C, more preferably 1.05 to 1.6 × 10 -4 / ° C. Furthermore, the release film of the present invention has a ratio of the linear expansion coefficient in the MD direction to the linear expansion coefficient in the TD direction (MD / TD) of preferably 1.0 to 2.5, more preferably 1.1 to 2.2, and even more preferably 1.2 to 2.0.
[0067] If the release film of the present invention satisfies the above-mentioned requirements regarding the linear expansion coefficient, it is preferable from the viewpoint of conformability to irregularities when molding a carbon fiber composite material (CFRP).
[0068] <Laminated film> In addition to the monolayer film obtained from the above-mentioned composition (X), the release film of the present invention is also preferably a laminate film in which at least one outermost layer is made of the composition (X).
[0069] The layer configuration of the laminated film may be, for example, a film having a five-layer structure consisting of Layer A (surface layer), Layer B (adhesive layer), Layer C (base layer), Layer B' (adhesive layer) and Layer A' (surface layer). In this case, Layer A (surface layer) and Layer A' (surface layer) are preferably layers consisting of the composition (X).
[0070] Examples of resins constituting the base layer include low-density polyethylene, linear low-density polyethylene, high-density polyethylene, propylene homopolymer, ethylene-propylene copolymer, ethylene-propylene-butene copolymer, butene homopolymer, ethylene-butene copolymer, propylene-butene copolymer, poly4-methyl-1-pentene, ethylene-α-olefin copolymer, propylene-α-olefin copolymer, 1-butene-α-olefin copolymer, Polyamide resins such as polyamide 6, polyamide 11, polyamide 12, polyamide 612, polyamide 66, polyamide 610, polyamide 46, polyamide MXD6, polyamide 6T, polyamide 6I, polyamide 9T, etc. Examples of suitable polymers include polyester resins such as polyethylene terephthalate and polybutylene terephthalate, polycarbonate resins, vinyl chloride, vinylidene chloride, polyurethane, ethylene-acrylic acid ester copolymers, ethylene-methacrylic acid ester copolymers, ethylene-vinyl acetate copolymers, ethylene-acrylic acid copolymers, ethylene-methacrylic acid copolymers, and partially ionically crosslinked products thereof.
[0071] As the resin constituting the base layer, the above-mentioned resins may be used alone or in combination of two or more. The adhesive layer may be made of, for example, a polyolefin resin modified with an unsaturated carboxylic acid or an unsaturated carboxylic anhydride, more specifically, a resin containing a modified poly-4-methyl-1-pentene polymer.
[0072] The method for obtaining the laminated film is not particularly limited, and examples thereof include a method in which a surface layer film previously obtained by extrusion casting or inflation molding is laminated by a known lamination method such as extrusion lamination or extrusion coating, or a method in which multiple films are molded independently and then each film is laminated by dry lamination. From the viewpoint of productivity, however, co-extrusion molding in which multiple components are fed into a multi-layer extruder and molded is preferred.
[0073] The thickness of the release film of the present invention is not particularly limited, but is usually 500 μm or less, preferably 10 to 500 μm, more preferably 20 to 250 μm, and further preferably 20 to 100 μm.
[0074] [Application] The release film of the present invention can be used for various purposes, but can be particularly suitably used as a release film for molding fiber-reinforced resins such as carbon fiber composites (CFRP). When the release film of the present invention is used as a release film for molding fiber-reinforced resins, it has the same heat resistance and releasability as conventional release films, while allowing fine processing of fiber-reinforced resin molded bodies, no film remains on the molded body when peeled off, and when the release film is attached to the molded body, it has good visibility and the attached release film can be easily recognized. EXAMPLES
[0075] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention. The materials used in the examples and comparative examples are shown below.
[0076] [4-methyl-1-pentene (co)polymer (A)] Preparation of polymer (A-1) Polymer (A-1), which is a 4-methyl-1-pentene (co)polymer (A), was obtained by changing the ratio of 4-methyl-1-pentene, other α-olefins (mass mixture of 1-hexadecene, 1-octadecene, etc.), and hydrogen in accordance with the polymerization method described in Comparative Example 9 of WO 2006 / 054613. The physical properties of polymer (A-1) are shown in Table 1.
[0077] [4-methyl-1-pentene copolymer (B)] Production of copolymer (B-1) A 1.5-liter stainless steel autoclave equipped with an agitator and thoroughly purged with nitrogen was charged with 300 ml of normal hexane (dried over activated alumina in a dry nitrogen atmosphere) and 450 ml of 4-methyl-1-pentene at 23° C. 0.75 ml of a 1.0 mmol / ml toluene solution of triisobutylaluminum (TIBAL) was charged into the autoclave and the agitator was turned on.
[0078] Next, the autoclave was heated to an internal temperature of 60°C, and pressurized with propylene so that the total pressure was 0.19MPa (gauge pressure). Then, 0.34ml of a toluene solution containing 1mmol of methylaluminoxane in terms of Al and 0.01mmol of diphenylmethylene (1-ethyl-3-t-butyl-cyclopentadienyl) (2,7-di-t-butyl-fluorenyl) zirconium dichloride, which had been prepared in advance, was pressed into the autoclave with nitrogen to start polymerization. During the polymerization reaction, the temperature was adjusted so that the internal temperature of the autoclave was 60°C. 60 minutes after the start of polymerization, 5ml of methanol was pressed into the autoclave with nitrogen to stop the polymerization, and the autoclave was depressurized to atmospheric pressure. Acetone was poured into the reaction solution while stirring.
[0079] The obtained powdery polymer containing the solvent was dried at 100°C under reduced pressure for 12 hours to obtain copolymer (B-1), which is 4-methyl-1-pentene copolymer (B). The obtained copolymer (B-1) weighed 44.0 g, and the 4-methyl-1-pentene content in copolymer (B-1) was 85 mol%, and the propylene content was 15 mol%. The physical properties of copolymer (B-1) are shown in Table 1.
[0080] Production of copolymer (B-2) A 1.5-liter stainless steel autoclave equipped with an agitator and thoroughly purged with nitrogen was charged with 300 ml of normal hexane (dried over activated alumina in a dry nitrogen atmosphere) and 450 ml of 4-methyl-1-pentene at 23° C. 0.75 ml of a 1.0 mmol / ml toluene solution of triisobutylaluminum (TIBAL) was charged into the autoclave and the agitator was turned on.
[0081] Next, the autoclave was heated to an internal temperature of 60°C, and pressurized with propylene so that the total pressure was 0.40MPa (gauge pressure). Then, 0.34ml of a toluene solution containing 1mmol of methylaluminoxane in terms of Al and 0.01mmol of diphenylmethylene (1-ethyl-3-t-butyl-cyclopentadienyl) (2,7-di-t-butyl-fluorenyl) zirconium dichloride, which had been prepared in advance, was pressed into the autoclave with nitrogen to start polymerization. During the polymerization reaction, the temperature was adjusted so that the internal temperature of the autoclave was 60°C. 60 minutes after the start of polymerization, 5ml of methanol was pressed into the autoclave with nitrogen to stop the polymerization, and the autoclave was depressurized to atmospheric pressure. Acetone was poured into the reaction solution while stirring.
[0082] The obtained powdery polymer containing the solvent was dried at 100°C under reduced pressure for 12 hours to obtain copolymer (B-2), which is 4-methyl-1-pentene copolymer (B). The obtained copolymer (B-2) weighed 36.9 g, and the 4-methyl-1-pentene content in copolymer (B-2) was 72 mol%, and the propylene content was 28 mol%. The physical properties of copolymer (B-2) are shown in the table.
[0083] [Coloring component (C)] CI Pigment White 6 and CI Pigment Blue 15:3 were used as coloring components (C).
[0084] [Colorant masterbatch] Manufacture of colorant master batch (C-1) The polymer (A-1) was blended with CI Pigment White 6 at a content of 0.5%, CI Pigment Blue 15:3 at a content of 3%, magnesium stearate at a content of 3%, and zinc stearate at a content of 3%, and melt-kneaded in a twin-screw extruder (Ikegai Corporation, PCM45, φ=45 mm, L / D=30) at a cylinder temperature of 270°C and a rotation speed of 150 rpm to obtain a colorant master batch (C-1). The methods for measuring the physical properties of the polymer are shown below.
[0085] <Content (mol %) of each structural unit of the polymer> The content (mol%) of each structural unit is given under the following conditions: 13 The measurements were performed using C-NMR.
[0086] ~Conditions~ Measurement equipment: Nuclear magnetic resonance equipment (ECP500 type, manufactured by JEOL Ltd.) Observation kernel: 13 C(125MHz) Sequence: Single pulse proton decoupling Pulse width: 4.7μsec (45° pulse) Repeat time: 5.5 seconds Number of times: 10,000 or more Solvent: orthodichlorobenzene / deuterated benzene (volume ratio: 80 / 20) mixed solvent Sample concentration: 55mg / 0.6mL Measurement temperature: 120℃ Chemical shift reference value: 27.50 ppm
[0087] <Intrinsic viscosity [η]> The intrinsic viscosity [η] of the polymer was measured by the following method using an Ubbelohde viscometer. 20 mg of polymer (A) is dissolved in 25 ml of decalin to obtain a decalin solution, and then the specific viscosity ηsp is measured using an Ubbelohde viscometer in an oil bath at 135°C. This decalin solution is diluted by adding 5 ml of decalin, and the specific viscosity ηsp is measured in the same manner as above. This dilution procedure is repeated two more times, and the value of ηsp / C when the concentration (C) is extrapolated to 0 is taken as the limiting viscosity [η] (unit: dl / g) (see the formula below). [η]=lim(ηsp / C) (C→0)
[0088] <Melting point (Tm)> The melting point (Tm) of the polymer was measured by the following method in accordance with JIS K7121 using a differential scanning calorimetry (DSC).
[0089] Approximately 5 mg of the polymer was sealed at room temperature in an aluminum pan for measurement of a differential scanning calorimeter (DSC220C type) manufactured by Seiko Instruments Inc., and heated from room temperature to 280°C at a rate of 10°C / min. In order to completely melt the polymer, it was held at 280°C for 5 minutes, and then cooled to -50°C at a rate of 10°C / min. After holding at -50°C for 5 minutes, it was heated a second time to 280°C at a rate of 10°C / min, and the temperature at which a peak was observed during this second heating was taken as the melting point (Tm) of the polymer. When multiple peaks were detected, the peak detected on the highest temperature side was adopted.
[0090] [Table 1]
[0091] (Examples 1 to 7, Comparative Examples 1 to 4) The compositions (X) according to Examples 1 to 7 and Comparative Examples 1 to 4 were produced by blending the polymer (A), the copolymer (B) and the colorant master batch (C-1) so that the contents of the polymer (A), the copolymer (B) and the colorant component (C) were the amounts shown in Table 2, and kneading them in a single-screw extruder (TP20 type) manufactured by Thermo Plastics Industries Co., Ltd., and further extruding them under conditions of a cylinder temperature of 280°C, a die temperature of 280°C and a roll temperature of 60°C to obtain an extruded film having a thickness of about 30 μm as a release film. The obtained extruded film was subjected to the following measurements and evaluations.
[0092] (Tensile elongation at break, tensile stress at break) The tensile elongation at break and the tensile stress at break were measured in accordance with JIS K67817127 using the extruded film as a test piece at a tension speed of 200 mm / min with an Instron Universal Tensile Tester 3380.
[0093] (Tear strength) The tear strength was measured in accordance with JIS K7128 using the extruded film as a test piece at a tensile speed of 200 mm / min using a universal tensile tester 3380 manufactured by Instron Corporation.
[0094] (Linear expansion coefficient) The linear expansion coefficient was measured by the TMA method under the following conditions: temperature rise 5°C / min, sample size 4mm width, chuck distance 10mm, and measurement load 49mN. The linear expansion coefficient was measured in the range of 23°C to 180°C. The equipment used was a TMA-SS120 manufactured by Seiko Instruments Inc.
[0095] (Total light transmittance TT) The total light transmittance TT was evaluated in accordance with JIS K7136 using the extruded film as a test piece and MNDH2000 manufactured by Nippon Denshoku Industries Co., Ltd.
[0096] [Evaluation of release films for carbon fiber composites] Four layers of prepreg, in which carbon fiber was impregnated with resin, were stacked to a thickness of 1 mm, and a mold was used to vacuum-bag mold the prepreg at 180°C for 2 hours under 0.3 MPa to produce a molded body of the carbon fiber composite material. During molding, the extruded films obtained in the Examples and Comparative Examples were placed above and below the laminated prepreg as release films, sandwiching the prepreg between them.
[0097] (Film visibility) The visibility of the release film was evaluated visually using the following indices. ○: The film can be seen on the carbon fiber composite material. ×: No film is visible on the carbon fiber composite material.
[0098] (Conforms to uneven surfaces after molding) The ability of the release film to conform to the irregularities of the mold after molding was evaluated using the following index. ◯: No film wrinkles were generated and the film conformed to the uneven surface of the mold. △: Some film wrinkles occurred, but the film conformed to the uneven parts of the mold. ×: Not conforming to the uneven parts of the mold.
[0099] (Ease of peeling off film after molding) The ease of peeling off the release film after molding was evaluated using the following index. Good: The film peels off without resistance or force when peeling off. △: There is some resistance when peeling off, but the film can be peeled off. ×: Does not peel off.
[0100] (Surface appearance of molded product) The appearance of the surface of the molded article was visually evaluated according to the following criteria. ◯: The molded article has a uniform appearance and excellent gloss. Δ: The molded product has a uniform appearance, but is slightly inferior in gloss. ×: The molded product has a non-uniform appearance. Specifically, the term "uneven appearance" refers to the transfer of film wrinkles caused by thermal deformation to the molded article, or the occurrence of partial scratches or dents caused by the film biting into the molded article.
[0101] [Table 2]
Claims
1. 60 to 95% by mass of a 4-methyl-1-pentene (co)polymer (A) satisfying the following requirements (A-a) to (A-c); 5 to 40% by mass of a 4-methyl-1-pentene copolymer (B) satisfying the following requirements (Ba) to (Bc) (the total amount of the (co)polymer (A) and the copolymer (B) is taken as 100% by mass), A layer made of a composition (X) containing A single-layer or multi-layer release film having a total light transmittance of less than 80% as measured using a film having a thickness of 30 μm in accordance with JIS K7136. (A-a) The content of the structural unit (P) derived from 4-methyl-1-pentene is 90 to 100 mol %, and the content of the structural unit (AQ) derived from ethylene and an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is 0 to 10 mol % (the total content of the structural unit (P) and the structural unit (AQ) is 100 mol %). (Ab) The intrinsic viscosity [η] measured in decalin at 135° C. is 0.5 to 5.0 dl / g. (Ac) The melting point (Tm) measured by DSC is in the range of 200 to 250°C. (Ba-a) The content of the structural unit (P) derived from 4-methyl-1-pentene is 65 to 72 mol %, and the content of the structural unit (BQ) derived from at least one selected from ethylene and an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is 28 to 35 mol % (the total content of the structural unit (P) and the structural unit (BQ) is 100 mol %). (Bb) The intrinsic viscosity [η] measured in decalin at 135° C. is 0.5 to 5.0 dl / g. (Bc) The melting point (Tm) as measured by DSC is not confirmed or is in the range of 100 to 199°C.
2. The linear expansion coefficient from 23°C to 180°C is 1.0 to 1.7 x 10 in the MD direction. -4 / °C, and the ratio of the linear expansion coefficient in the MD direction to the linear expansion coefficient in the TD direction (MD / TD) is 1.0 to 2.
5.
3. 3. The release film according to claim 1, wherein the structural unit (BQ) is a structural unit derived from at least one selected from ethylene and an α-olefin having 3 to 4 carbon atoms.
4. The release film according to any one of claims 1 to 3, further comprising a coloring component (C).
5. The release film according to any one of claims 1 to 4, which is for fiber reinforced resin molding.
Citation Information
Patent Citations
Release film
JP1995009625A
Highly crystalline poly-4-methylpentene resin composition and film
JP2005350601A
Manufacturing method of printed wiring board
JP2010027745A
Release film
JP2014098138A
Film containing 4-methyl-1-pentene-based polymer-containing resin composition
JP2016098257A
